The Maria asteroid family - Aljbaae, S. [UNESP]; Carruba, V. [UNESP]; Masiero, J. R.; Domingos, R. C. [UNESP]; Huaman, M. [UNESP] (Oxford University Press (OUP), 2017)
The Maria asteroid family is a group of S-type asteroids. Its location adjacent to the left side of the 3J:-1A mean-motion resonances could be the reason for the absence of the left side of the 'V' shape in the (a, 1/D) domain. This family can be considered as a likely source of ordinary chondrite-like material. In this work, we make use of the time dependence of the asymmetric coefficient AS describing the degree of asymmetry of the C distribution of a fictitious Maria family generated with the value of the ejection velocity parameter VEJ = 35ms-1 to obtain an age estimate of 1750 +537 -231 Myr, in good agreement with the family age found in the literature. Analysing the contribution to the near-Earth object (NEO) population, we found that about 7.6 per cent of presently known near-Earth asteroids (NEAs) have orbits similar to asteroids from the Maria family. Only ~1.7 per cent of our simulated family can stay in NEO space for more than 10 Myr, while only five asteroids become NEOs in the last 500 Myr of the simulation.
Keywords: Asteroids: general; Celestial mechanics; Gravitation; Minor planets